A Indústria têxtil brasileira e suas adequações na implementação do desenvolvimento sustentável (ModaPalavra e-periódico, 2014)
The domestic textile industry is the fifth largest in the world, however, its constitution and its complex fragmented supply chain end up not collaborate in order to legitimize their political, social and economic force. However, the industry is preparing to achieve goals of social and environmental responsibility and position themselves were aligned with global expectations of sustainable growth. This research is exploratory character and bibliography, and proposes to analyze the situation of the domestic textile park by the insurgency of environmental matter and try to understand why fashion-sustainability relationship is challenged as a dichotomous relationship. The references used were based on data provided by the formal representative organs in the sector, and authors in the field of environmental science and fashion.
Keywords: fashion; textile Industry; sustainability; environment